مقاصد شریعہ تابعین و مابعد ائمہ اربعہ کے عہد میں: Objectives of the Shariah in the period of Tabi’een and After them - Dr. Zaheer ul Deen Babar,; Dr. Abdul Raouf Usmani,; Dr Muhammad Inamullah, (Al Manhal Research Journal, 2024)
The kind of Ijtihad is being mostly used for the solution of complex and difficult issues in the contemporary age that is Ijtihad-e-Istislahi or Maqasid-E-Shari'ah refers to the goals and objectives that have been observed in Shariah orders. These goals can be partial Wisdoms, overall Interests or just Summary signs. And the aim of all these goals is to achieve the pleasure of God and the success of Daryn. Ilm-E-Maqasid-E-Shari'ah is not a new knowledge, its foundations like other Islamic studies are also found in the phase of Nabvi (S.A.W). In many orders issued in the Prophecy, we find examples of how the Maqasid-E-Shari'ah were kept for consideration. In the phase of Sahaba (R.A) the decisions made under Ijtihad Bil Rai indicate that the rules of Jalb-E-Manfait and Dafa-E-Haraj were also used to them. In the phase of Tabaeen and Aima arba the terms of Masalih-E-Mursalah, Ijtihad bil Masliha and Qayas-e- Mursal etc were used for Ilm-E-Maqasid-E-Shari'ah